Implementasi Metode Naive Bayes-Certainty Factor Untuk Identifikasi Penyakit Kanker Pada Sistem Reproduksi Wanita - Muhammad Anang Mufid; Nurul Hidayat; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
There are many women who still reluctant to pay attention to the health of the reproductive system. Cancer can attacks slowly if women don't maintain the health of their reproductive system. Cancer prevention is very necessary nowadays, but sometimes it stumbled on the limited number of doctors or experts. Therefore, a tool of expert system need to be made to reduce these limitiations. This study implements an expert system to diagnose cancer in the reproductive system using the android-based Naive Bayes-Certainty Factor method. Based on trials, by using Naive Bayes-Certainty Factor method, the calculation accuracy of the diagnose is good and accurate, the calculation accuracy of the diagnose is good and accurate, because the output of system has 85,71% as accurity level.